2007
DOI: 10.1089/acm.2006.6225
|View full text |Cite
|
Sign up to set email alerts
|

Use of Traditional Medicine among Pregnant Women in Lusaka, Zambia

Abstract: Use of traditional medicine during pregnancy is common, stigmatized, and may be associated with nonadherence to antiretroviral regimens. Health care providers must open lines of communication with traditional healers and with pregnant women themselves to maximize program success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 21 publications
5
68
1
1
Order By: Relevance
“…This may be because of the attitude and or perceptions of HCWs who tend to discourage ART patients about the toxicity effects of TM. These findings confirm those reported in Zambia, where 64% of pregnant women seeking care from THPs would not want to share this information with their obstetric provider and 54% thought that admitting to seeing a traditional healer would negatively impact their antenatal care (Banda et al, 2007). Besides the fact that HCWs were concerned about the toxicity effects of using both ARTs and TM, most of the participants indicated that they didn't want to disclose their status or to be seen at the facility by everybody.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This may be because of the attitude and or perceptions of HCWs who tend to discourage ART patients about the toxicity effects of TM. These findings confirm those reported in Zambia, where 64% of pregnant women seeking care from THPs would not want to share this information with their obstetric provider and 54% thought that admitting to seeing a traditional healer would negatively impact their antenatal care (Banda et al, 2007). Besides the fact that HCWs were concerned about the toxicity effects of using both ARTs and TM, most of the participants indicated that they didn't want to disclose their status or to be seen at the facility by everybody.…”
Section: Discussionsupporting
confidence: 80%
“…For example, a study conducted among pregnant women highlighted that 64% of participants sought care from a traditional healer, but they would not share this information with their obstetric provider; 54% stated that admitting to seeing a traditional healer would have a negative impact on their antenatal care. Among HIV pregnant mothers on Nevirapine 50% non-adheres had used traditional medicine compared to only 25% of the adherers (Banda, 2007). Although there is evidence in the literature that has proven the wide use of THP in combination with Western medicine, less is known of the perceptions of healthcare providers and HIV patients on prophylaxis and use of combination of THP and ART/other prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…This may be unt rue, as the pills are given to patients for free and can be explained by the patients resorting to using herbal medicines. Similar studies carried out by Peltzer et al (2008) and Banda et al (2007) have shown that patients using herbal treatments in conjunction with ART are more likely to take gaps in treatment or reduce their level of adherence. Also, majority of the respondents (66.1% ) stated that they are not part of a support group.…”
Section: Resultsmentioning
confidence: 57%
“…This suggests an opportunity to instill long lasting modern health care messages which are likely to be well taken up as is the case with traditional beliefs provided the messages are linked with live examples of health benefits. Communities followed traditional norms that had no health benefits and to some were detrimental to their health (Banda et al, 2007;Kamatenesi-Mugisha and Oryem-Origa, 2006). Interestingly, customs such as wife inheritance and temporal allowance of fertile men to sleep with women whose men were infertile through mutual agreement is dying away due to HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%